Evaluation of the usefulness of FDG-PET/CT in diagnosis and qualification for surgical treatment of advanced gastric cancer - Staniuk, Tomasz; Jankowski, Michał; Zegarski, Wojciech; Małkowski, Bogdan; Kula, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2010)
Aims : Evaluation of FDG-PET usefulness in diagnosis and qualification for surgical treatment of advanced gastric cancer. Material and methods : Sixteen advanced gastric cancer patients (T2,N0-3,M0-1) who underwent FDG-PET/CT imaging and surgical treatment were evaluated retrospectively. Detailed data influencing cancer detection such as primary tumour size, depth of invasion, histological and Lauren classification type as well as tumour location were analysed. Correspondence between FDG-PET/CT and postoperative histopathological evaluation of nodal involvement was assessed. Results : 60% of tumours larger than 4 cm, 75% of pT2 and pT3 tumours, 60% of mucocellular type and 75% of poorly or undifferentiated type tumours, and 77% of non-intestinal Lauren type tumours were detected. No tumour smaller than 4 cm was identified. 75% of tumours located in the middle one-third of the stomach were not detected. Also no resectable gastric cancer patient with nodal involvement was N(+) with FDG-PET/CT. Conclusions : 1. Primary tumour size and location may influence FDG-PET/CT results. 2. FDG-PET/CT is not a sufficient method of detection of all histological types of gastric cancer. 3. FDG-PET/CT is not a sufficient method of preoperative assessment of perigastric lymph nodes; thus this examination does not enable proper qualification for radical operative treatment in advanced gastric cancer (T2-4,N0-3,M0-1). 5. Detection of increased FDG uptake in perigastric lymph nodes may support unresectability of gastric cancer.